2021
DOI: 10.3390/jof7100869
|View full text |Cite
|
Sign up to set email alerts
|

The Mycorrizal Status in Vineyards Affected by Esca

Abstract: In this work we analyzed the relationship among native arbuscular mycorrhizal fungi (AMF) and vine roots affected by esca, a serious grapevine trunk disease. The AMF symbiosis was analyzed on the roots of neighboring plants (symptomatic and asymptomatic to esca) in 14 sites of three vineyards in Marche region (central–eastern Italy). The AMF colonization intensity, identified by non-vital staining, showed higher value in all esca symptomatic plants (ranging from 24.6% to 61.3%) than neighboring asymptomatic pl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 80 publications
(89 reference statements)
0
4
0
Order By: Relevance
“…A particular interaction was discussed by Landi et al [229]. Their study suggested a relationship between esca disease and native AMF in grapevine roots.…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 94%
“…A particular interaction was discussed by Landi et al [229]. Their study suggested a relationship between esca disease and native AMF in grapevine roots.…”
Section: Arbuscular Mycorrhizal Fungi (Amf)mentioning
confidence: 94%
“…The primer pair DBF1/R1 was tested in qPCR. The analytical sensitivity (limit of detection; LOD, Bustin et al, 2009 ) was assessed using serial dilutions (285 ng, 57 ng, 20 ng, 11.4 ng, 2.28 ng, 4.56 × 10 –1 ng, 9.12 × 10 –2 ng, 1.82 × 10 –2 ng, 3.6 × 10 –3 ng, 7.2 × 10 –4 ng, 1.45 × 10 –4 ng, and 2.9 × 10 –5 ng) of DNA extracted from the mycelia of S. cucurbitacearum isolate D33 spiked with 20, 57, and 285 ng of DNA from healthy seeds in qPCR ( Landi et al, 2021 ). The reactions were carried out in a total volume of 12 μl containing: 2× Master mix iTaq Universal SYBR Green Supermix (Bio-Rad Laboratories, Hercules, CA, United States), and 0.10 μM of the designed primers (DBF1/R1).…”
Section: Methodsmentioning
confidence: 99%
“…Since the early 1990ies, numerous studies have shown that multiple biotic and abiotic factors, as well as agronomic practices, are correlated to onset, discontinuity, incidence and severity of the leaf stripe symptom (Table 1;Fischer and Ashnaei, 2019;Claverie et al, 2020;Del Frari et al, 2021). Among these, meteorological conditions (e.g., rainfall, drought, temperature, soil moisture) play major roles in yearly symptom fluctuations (Surico et al, 2000;Marchi et al, 2006;Bruez et al, 2013;Andreini et al, 2014; Grapevine age e Water availability l Fungal endophytes (wood pathogens and/ or biocontrol agents) f Rhizosphere microbiome g a Lecomte et al, 2011;Fischer andAshnaei, 2019 b Christen et al, 2007;Magnin-Robert et al, 2011;Fontaine et al, 2016a;Goufo and Cortez, 2020;Calvo-Garrido et al, 2021c Pouzoulet et al, 2014d Marchi, 2001Bruez et al, 2013;Andreini et al, 2014;Murolo and Romanazzi, 2014;Pouzoulet et al, 2014;Borgo et al, 2016e Mugnai et al, 1999Graniti et al, 2000;Surico et al, 2008 f Larignon andDubos, 1997;Peros et al, 2008;Bigot et al, 2020;Nerva et al, 2019;Del Frari et al, 2021;Fotios et al, 2021;Di Marco et al, 2022g Landi et al, 2021h Surico et al, 2000Marchi et al, 2006;Bruez et al, 2013;Calvo-Garrido et al, 2021i Di Marco et al, 2011Songy et al, 2019;…”
Section: Introductionmentioning
confidence: 99%
“…This confirms that the microbiological aspect of the wood of leaf symptomatic vines is only one of the factors of a bigger equation. For example, even the grapevine rhizosphere, in particular arbuscular mycorrhizal fungi, may alter their abundance in leaf symptomatic vines (Landi et al, 2021).…”
Section: Introductionmentioning
confidence: 99%